Food safety and food quality - Hester, R. E.; Harrison, Roy M., 1948- (Issues in environmental science and technology ;, 2001)
The quality and safety of the food we eat attracts a great deal of publicity and is high on the list of public concerns. This highly emotive issue is discussed in this timely book, which brings together a group of experts to present up-to-date and balanced overviews on a wide range of topics including GM crops; hazardous microorganisms such as E. coli; the BSE/CJD problem; and cancer-causing chemicals, both natural and synthetic. Thought-provoking and of interest to a wide readership, this authoritative review will be welcomed by food scientists, legislators, government officials and advisors. Students of food science or environmental science will also find it essential reading.